Endoscopic endonasal management of skull base defects in pediatric patients. (November 2021) - Iranmehr, Arad; Zeinalizadeh, Mehdi; Namvar, Mohamad; Fathi, Ali; Azimi, Hesam; Tabari, Azin; Sadrehosseini, Seyed Mousa
Abstract: Purpose: Skull base defects in children may be the result of congenital anomalies or trauma. They often present as cerebrospinal fluid (CSF) rhinorrhea, meningitis, brain abscess or nasal obstruction. Surgical intervention is predominantly the treatment of choice. Our goal is to assess the efficacy of endoscopic endonasal approach in treating skull base defects in pediatric patients. Material and methods: In this retrospective study we identified 38 patients (mean age 8.7 ± 5.6 years old, ranging 2 months-18 years) who underwent endoscopic endonasal repair of skull base defects, between March 2010 and February 2020. Patients who had skull base reconstruction after tumor resection, those who were lost to follow-up or did not sign the consent forms were excluded from the study. Results: The clinical indications for endoscopic endonasal repair were trauma (n = 24, 63.1%) and congenital defects (n = 14, 36.9%). Congenital skull base defects included basal meningoencephalocele (n = 5, 35.7%) and frontoethmoidal defects (n = 9, 64.3%). Mean follow up time was 32 ± 29.04 months, ranging 2–103 months. Fat graft (alone or in combination) was the most commonly used material to repair the skull base defects. Thirty-seven patients (97%) showed successful results after endoscopic endonasal surgery and were symptom free. Conclusion: The endoscopic endonasal repair of CSF leak and skull base defects proved to be safe and feasible with 97% success rate.